Kyphoplasty for osteoporotic vertebral fractures: Epidemiology and clinical-radiological outcomes - Hendra; Agus Hadian Rahim; Ahmad Ramdhan; Abdul Kadir Hadar; Renata Junilla (Physical Therapy Journal of Indonesia, 2026)
Background: Osteoporotic vertebral fractures (OVFs) are the most common complication of osteoporosis and a significant public health burden. Kyphoplasty is a minimally invasive surgical option that can restore vertebral body height and reduce deformity. This study aimed to describe the epidemiological characteristics, clinical profile, and radiological outcomes of OVFs patients treated with kyphoplasty at Hasan Sadikin General Hospital, Indonesia. Methods: A retrospective observational study was conducted on patients with OVFs who underwent kyphoplasty between January 2020 and August 2025 at Hasan Sadikin General Hospital, Indonesia. Demographic data, fracture characteristics, and radiological parameters (Beck’s index, local kyphotic angle) were collected. Continuous variables were reported as median and range; categorical variables as frequency and percentage. Results: Twenty patients were included (15 females, 75%; 5 males, 25%), with a median age of 67 years (range: 46–87). Fractures involved the thoracic (45%), lumbar (35%), and thoracolumbar (20%) regions. Compression fractures were most common (45%), followed by burst (30%) and mixed patterns (25%). Single-level involvement occurred in 65% of patients. Postoperative radiographs demonstrated significant improvements: Beck’s index increased from 58% preoperatively to 69% postoperatively (+19%), and local kyphotic angle improved from 14.9° to 10.3° (–28%). Conclusion: Kyphoplasty was effective in restoring vertebral height and correcting kyphotic deformity in patients with OVFs. Older women were most commonly affected, reflecting the epidemiological burden of osteoporosis in Indonesia. These findings support kyphoplasty as a valuable treatment option in selected OVF patients.